Materiales poliméricos compuestos con polietileno (PEBD) y fibras del árbol Maclura tinctoria (Moraceae) - Nikolaeva, S. (2015)
Costa Rica has extensive areas of tropical forests that, managed with care and knowledge, can provide renewable raw materials and conserve biodiversity. Here we characterize the branches, leaves and bark of the “Mora Tree”, Maclura tinctoria. We manufactured composite polymeric materials and applied infrared spectrometry, liquid chromatography, optical microscopy, and the analysis of thermal and mechanical properties. We found polyphenols in all parts of the tree. The natural substrate increases crystallization temperature and reduces the crystallinity of low density polyethylene (LDPE). The elasticity modulus is higher for the composite material than for the LDPE. The fibers of this species are a promissing alternative for new products and to reduce the environmental impact of traditional polymeric materials.